Inclusive Education: Necessity, Prospective Trend - Jahangir, Abdullayev; Shonazar, Botirov (Indonesian Journal Publisher, 2024)
This article describes the introduction of inclusive education, what it is, about children with disabilities, as well as the positive and negative aspects of inclusive education. Employing a thorough research methodology that involves a systematic literature review and analysis of empirical studies, the study synthesizes existing knowledge on inclusive education. The results illuminate the positive outcomes, such as enhanced social integration and academic achievement, as well as the challenges, including potential resource constraints and the need for tailored support systems. The discussion delves into the nuanced dynamics of inclusive education, weighing its merits and demerits while addressing the broader implications for educational policies and practices. Through this comprehensive approach, the article contributes to a deeper understanding of the complex interplay between inclusive education, disability, and the broader educational landscape.